2009
DOI: 10.1177/1524838009339755
|View full text |Cite|
|
Sign up to set email alerts
|

From the Margins to the Center

Abstract: The trauma of sexual assault is heightened for many women by the interlocking experience of societal traumas such as racism, sexism, and poverty. The mental health effects of sexual assault are mediated by race and ethnicity. The investigators explore the experiences of African American, Asian American, Latina, and Native American female survivors of sexual assault. The sociohistorical context of intergenerational trauma in the lives of ethnic minorities is a part of the context for the contemporary experience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
80
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(82 citation statements)
references
References 175 publications
(190 reference statements)
2
80
0
Order By: Relevance
“…Childhood sexual abuse (CSA), most often defined as unwanted sexual contact or intercourse that occurs between a child and an older individual (often a family member or individual in a caretaking role such as a physician, babysitter, or teacher; Bulik, Prescott, & Kendler, 2001;van Roode, Dickson, Herbison, & Paul, 2009), and adolescent/adult sexual assault (ASA), most often defined as sexual acts obtained by threat, force, or against someone who is not capable of consenting (such as because of incapacitation following substance use; Zinzow et al, 2012), have repeatedly been associated with negative mental health outcomes. Outcomes that consistently have been found to be associated with sexual victimization include depression, anxiety, posttraumatic stress disorder (PTSD), and substance use disorders (Bulik et al, 2001;Danielson et al, 2010;Walsh, Galea, & Koenen, 2012;Zinzow et al, 2012).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Childhood sexual abuse (CSA), most often defined as unwanted sexual contact or intercourse that occurs between a child and an older individual (often a family member or individual in a caretaking role such as a physician, babysitter, or teacher; Bulik, Prescott, & Kendler, 2001;van Roode, Dickson, Herbison, & Paul, 2009), and adolescent/adult sexual assault (ASA), most often defined as sexual acts obtained by threat, force, or against someone who is not capable of consenting (such as because of incapacitation following substance use; Zinzow et al, 2012), have repeatedly been associated with negative mental health outcomes. Outcomes that consistently have been found to be associated with sexual victimization include depression, anxiety, posttraumatic stress disorder (PTSD), and substance use disorders (Bulik et al, 2001;Danielson et al, 2010;Walsh, Galea, & Koenen, 2012;Zinzow et al, 2012).…”
mentioning
confidence: 99%
“…Other studies have posited that engaging in sexual and other health risk behavior following sexual victimization may represent an effort to cope with psychological distress, including distress regarding sexual victimization experiences, other traumas, and general distress; this is termed the self-medication hypothesis (Bryant-Davis, Chung, & Tillman, 2009;Nguyen, Kaysen, Dillworth, Brajcich, & Larimer, 2010). Supporting this model, prior studies have found that higher levels of depression, PTSD, maladaptive abuse-related coping, and emotion dysregulation mediated the relationship between having a CSA history and engaging in sexual risk behavior in adulthood (Green et al, 2005;Merrill, Guimond, Thomsen, & Milner, 2003;Messman-Moore, Walsh, & DiLillo, 2010).…”
mentioning
confidence: 99%
“…Given White women are more likely to disclose this information to mental health professionals (Campbell, Wasco, Ahrens, Sefl, & Barnes, 2001), it is plausible ethnicity plays a significant role in the disclosure of SA experiences (Bryant-Davis, Chung, & Tillman, 2009;Starzynski, Ullman, Townsend, Long, & Long, 2007). There has been some qualitative exploration of this theme, with findings indicating several key reasons for nondisclosure by African American women such as racism within the community and criminal justice systems (Washington, 2001), more negative social reactions on disclosure (Ullman & Filipas, 2001), and skepticism of African American women's claims of assault (Donovan & Williams, 2002).…”
mentioning
confidence: 99%
“…African Americans live at disproportionately lower socioeconomic levels with less access to resources than their White counterparts (DeNavas-Walt, Proctor, & Smith, 2013). The added burden of traumatic SV victimization for women living in poverty potentially exacerbates the need for multiple services and resources to address various intersecting problems (i.e., poverty, victimization, mental and physical health; Bryant-Davis et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…In a U.S. national sample, a history of SV has been found to be associated with anxiety disorders, mood disorders, PTSD, SUDs, and suicide attempts (Iverson et al, 2013). Studies focusing on the mental and behavioral health of African American female SV survivors in particular are limited, and the studies that exist usually rely on urban, low socioeconomic status (SES), or drug-abusing samples (Boyd et al, 1997; Bryant-Davis, Chung, & Tillman, 2009; Bryant-Davis et al, 2010; Campbell et al, 2008; Vaszari, Bradford, CallahanO'Leary, Ben Abdallah, & Cottler, 2011). For example, in a community sample of low-income, ethnically diverse women ( N = 835), Temple and colleagues (2007) found that sexual assault by current partners and nonpartners was a significant predictor of PTSD symptoms for African American women.…”
Section: Health Risks and Adverse Conditions For African American Wommentioning
confidence: 99%